2010
DOI: 10.1021/jz100152j
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Defect Dynamics in Nanocrystalline CaF2: Results from 19F MAS NMR Spectroscopy

Abstract: The structure and F --ion dynamics in nanocrystalline CaF 2 is studied using 19 F fast magic angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy in the temperature range 22°C e T e 240°C. The 19 F MAS NMR spectra of nanocrystalline CaF 2 (diameter ∼ 25 nm) shows the presence of ∼0.55% of the F -ions in interstitial sites that are found to be highly mobile at elevated temperatures and undergo rapid site exchange with regular fluorine sites in the lattice via hopping. It is shown that an increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…The obtained ionic conductivity of synthesized polycrystalline solid CaF 2 electrolyte had been obtained to be 1.9 · 10 −5 S·cm −1 at room temperature, which is several orders of magnitude higher than that of pure and ball‐milled CaF 2 ‐reported values (2 · 10 −7 to 1.6 · 10 −11 S·cm −1 ) . The apparent ion mobilization activation energy of the electrolyte was estimated to be 0.35 eV, which had been reported to be related to the surface formation of interstitial fluoride sites with suggested formation energies of around 0.25 eV. Such activation energy makes the material more attractive as an ion conductor for fluoride shuttle applications.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The obtained ionic conductivity of synthesized polycrystalline solid CaF 2 electrolyte had been obtained to be 1.9 · 10 −5 S·cm −1 at room temperature, which is several orders of magnitude higher than that of pure and ball‐milled CaF 2 ‐reported values (2 · 10 −7 to 1.6 · 10 −11 S·cm −1 ) . The apparent ion mobilization activation energy of the electrolyte was estimated to be 0.35 eV, which had been reported to be related to the surface formation of interstitial fluoride sites with suggested formation energies of around 0.25 eV. Such activation energy makes the material more attractive as an ion conductor for fluoride shuttle applications.…”
Section: Resultsmentioning
confidence: 80%
“…Also, the introduction of defects and unit‐cell distortions, geometry frustration at grain boundaries of different crystallites, is reflected in an increase of line broadening . An additional small peak at −132 ppm can be assigned to mobile interstitial defect structures with large concentration at the surface with formation energies around 0.25 eV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous 19 F MAS NMR studies have shown that interstitial fluorine sites may be present in nanocrystalline CaF 2 at concentration levels of ∼0.5% and are characterized by 19 F chemical shift that is located significantly upfield compared with the 19 F chemical shift of regular F–Ca(4) lattice sites 25 . Therefore, the small but sharp peaks at −100 and −113 ppm in the 19 F NMR spectrum of the SrF 2 ‐oxyfluoride glass–ceramics (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…concentration levels of B0.5% and are characterized by 19 F chemical shift that is located significantly upfield compared with the 19 F chemical shift of regular F-Ca(4) lattice sites. 25 Therefore, the small but sharp peaks at À100 and À113 ppm in the 19 F NMR spectrum of the SrF 2 -oxyfluoride glass-ceramics ( Fig. 5) can possibly be attributed to interstitial fluorine sites inside the SrF 2 nanocrystals.…”
Section: Discussionmentioning
confidence: 97%